2011
DOI: 10.1038/nchembio.607
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and biology of reactive oxygen species in signaling or stress responses

Abstract: Reactive oxygen species (ROS) are a family of molecules that are continuously generated, transformed and consumed in all living organisms as a consequence of aerobic life. The traditional view of these reactive oxygen metabolites is one of oxidative stress and damage that leads to decline of tissue and organ systems in aging and disease. However, emerging data show that ROS produced in certain situations can also contribute to physiology and increased fitness. This Perspective provides a focused discussion on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
1,090
0
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,546 publications
(1,111 citation statements)
references
References 101 publications
(91 reference statements)
4
1,090
0
17
Order By: Relevance
“…inactivated phosphatases were hypothesized to shift the equilibrium of inactive to active kinases resulting in enhanced kinase activity (18,25,26). By now, a large number of redox modifications in phosphatases, kinases, adapters, receptors, and transcription factors have been proposed to modulate signaling, among them multiple components of the BCR signaling pathway such as tyrosine-protein kinase Lyn, tyrosine-protein kinase SYK (Syk), tyrosine-protein phosphatase nonreceptor types 6 and 11 (SHP1/PTPN6; SHP2/PTPN11), phosphatase and tensin homolog, and a mitogen activated protein (MAP) kinase serine/threonine phosphatase (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, it has been challenging to prove or disprove the physiological relevance of such a mechanism, and results have been difficult to reconcile as a whole (3,26,35).…”
mentioning
confidence: 99%
“…inactivated phosphatases were hypothesized to shift the equilibrium of inactive to active kinases resulting in enhanced kinase activity (18,25,26). By now, a large number of redox modifications in phosphatases, kinases, adapters, receptors, and transcription factors have been proposed to modulate signaling, among them multiple components of the BCR signaling pathway such as tyrosine-protein kinase Lyn, tyrosine-protein kinase SYK (Syk), tyrosine-protein phosphatase nonreceptor types 6 and 11 (SHP1/PTPN6; SHP2/PTPN11), phosphatase and tensin homolog, and a mitogen activated protein (MAP) kinase serine/threonine phosphatase (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, it has been challenging to prove or disprove the physiological relevance of such a mechanism, and results have been difficult to reconcile as a whole (3,26,35).…”
mentioning
confidence: 99%
“…In this study, we showed that RBOH-derived ROS production is required for robust RNA replication of RCNMV. Because ROS have generally short halflives and high reactivity within cells, spatial control of ROS generation sites is important for physiological ROS signaling (44). Here, we showed that the p27 replication protein of RCNMV interacts with and redistributes NbRBOHB from the PM to intracellular aggregate structures to induce ROS production in an RBOH activity-dependent manner (Figs.…”
Section: Discussionmentioning
confidence: 81%
“…These ROS are necessary for the signaling pathways in biological processes (3,4) such as cell migration, circadian rhythm, stem cell proliferation, and neurogenesis (5). In healthy systems, ROS are efficiently regulated by the defensive enzymes superoxide dismutase (SOD) and catalase, and by antioxidants such as glutathione, vitamin A, ascorbic acid, uric acid, hydroquinones, and vitamin E (6).…”
mentioning
confidence: 99%